An Integrative Model to Increase Client Motivation During the Psychotherapy Process - Eryilmaz, Ali; Doenyas, Ceymi (SPRINGER INT PUBL AG, 2025)
An effective psychotherapy process includes multiple elements, one of which is the client's motivation. While psychotherapy theories propose models to increase the functionality and well-being of clients, little is said about how to motivate clients along this process. Although client motivation is relevant for all major therapeutic approaches, there are not many investigations focusing mainly on this motivation, and especially exploring it in connection with the stages of the therapeutic process. Therefore, there is a need to understand the factors that motivate the clients in each stage of the psychotherapy and psychological counseling process. Many psychotherapy theories include these factors in their models, though they do not explicitly state them. This paper unravels these factors by presenting and integrating tools and strategies from multiple psychotherapy perspectives to increase and maintain client motivation during the therapeutic process. Using these tools and strategies is important, given that many clients skip or quit their psychotherapy sessions, which end up hindering or completely blocking the possibility to achieve the positive outcomes intended with the therapeutic process. The contribution of the present paper is synthesizing these tools and strategies within a single, staged therapeutic process model, which can be followed by therapists to increase therapy adherence and effectiveness.
Keywords: Client; Model; Motivation; Psychotherapy; Psychotherapist; Stage; THERAPY; SCIENCE; Psychology